A memória em Maria Valéria Rezende: do bios à palavra - CAMILA TORRES (2022)
This thesis proposed a study of the novelist role of Maria Valéria Rezende in the scope of her intellectual project as a whole. It was sought to present her contemporary novels published in 2014, linking them to the author’s life to which awards she received that has made her to be noticed by contemporary Brazilian literary critics. In this regard, when tracing a biographical profile of the author, it was sought to discuss an aspect of her project that arises in her works: her work as a popular educator of young and adult students in the countryside of Brazil through the articulation of memory. Whereas one side of her work, the feminine, marginalized people, her role as creator of Mulherio das Letras has gained strength and increased her critical fortune; on the other side, the relationship between life and work mediated by the risk of memory remains waiting for a more refined work. Thus, this thesis investigated the hypothesis that the author’s life contributed to her literary project and that memory does not pass unscathed in her work as a novelist. Under this aegis, two novels by Maria Valéria Rezende were analyzed with the objective of carrying out a critical-biographical reading of the and to present the extent to which memory is used as the craftsman of fiction. In this sense, the present thesis focused on the examination of the following novels O voo da guará vermelha and Quarenta dias. For this purpose, the studies of literary biographical criticism, postwestern literature and contemporary literature were taken as a theoretical contribution, with emphasis on the studies of Eneida Maria de Souza, Silviano Santiago, Leonor Arfuch, Diana Klinger, Walter Mignolo, Regina Dalcastagné and Beatriz Resende. Keywords: Maria Valéria Rezende; Memory; Narrative; Word.